Universal preference for Korean-type grapho-phonemic systematicity: a cross-cultural study of sound-symbol mapping in English, Chinese, and Korean speakers - Hana Jee (PLoS ONE, 2025)
Recent studies have revealed that writing systems exhibit systematic relationships between letter shapes and their corresponding sounds, termed ‘grapho-phonemic systematicity’. This systematicity manifests differently across writing systems: Semitic languages maximize systematicity through pixel count, Chinese through perimetric complexity, and Korean through Hausdorff distance. This study investigated whether native speakers of these languages would prefer the type of systematicity found in their respective writing systems. An online survey was conducted with 845 participants (271 British, 308 Chinese, and 266 Korean) who were asked to match novel symbols from archaic writing systems with given sound pairs. Contrary to the hypothesis that participants would prefer their native writing system’s systematicity pattern, all groups showed a stronger preference for Korean-type systematicity, where similar sounds correspond to topologically similar symbols. This unexpected finding suggests that modern humans might universally prefer certain types of symbol-sound mapping, possibly influenced by institutionalized education and formal logic training. Interestingly, Korean participants showed the least preference for Korean-type systematicity, potentially due to their meta-knowledge of Hangul’s intentional design. The study reveals a disconnect between how writing systems historically evolved and what modern humans prefer, suggesting that cognitive processes in symbol-sound mapping might have been shaped by modern educational frameworks. These findings contribute to our understanding of universal cognitive principles in visual-auditory mapping and the influence of cultural and educational factors on writing system preferences.